KARAKTERISTIK PANTAI INDRAMAYU KETERKAITANNYA DENGAN KEBERADAAN GAS BIOGENIK - Kurnio, H.; Naibaho, T.; Mustafa, M. Akrom (Pusat Survei Geologi, 2010)
Indramayu coast is characterized by sandy coastal dunes, with mangroves in between. The existence and conservation of mangroves are very important for biogenic gas occurences in this area; while the subsurface paleo sandy coastal dune sare strongly predicted as a gas reservoir. An inventory of Recent sandy dunes using coastal characteristic mapping method is important, because through dune identification; paleo-coastal dune condition that has already been in the subsurface can be identified. Detailed investigation is still required in order to truly invent this biogenic gas potency, before being utilized especially for the local community. The detailed exploration can be done through grid hand auger drillings combined with a subsurface radar for its lateral distributions.Keywords : coastal characteristics, biogenic gas, Indramayu